A Shout Against Silence: Language of Trauma and Post-Memory in "La voz dormida" by Dulce Chacón - Mininni, Maria Isabella (RiCOGNIZIONI. Rivista di Lingue e Letterature straniere e Culture moderne, 2020)
...